Production Of Braille Paper From Recycled Fiber Treated With Cellulose Acetate And Optimization By Response Surface Methodology (Rsm) - Soo, Mei Chong (2013)
Paper dust and oil palm empty fruit bunch (EFB) unbleached chemical pulps were derived to a low-grade cellulose acetate in this study. Papers made from secondary fiber were then treated with the resultant cellulose acetate (CA) to produce paper that is suitable to be used on Braille embosser but in lower grammage (~80 gsm) and higher paper stiffness. The treatment of cellulose acetate derived from paper dust (CAPD) into handsheet was studied statistically by employing a half two level factorial design. The effects of the three independent variables of treatment - dipping time, pressing temperature and pressing time on three response variables (paper density, burst index and rate of surface wettability) was investigated. The factorial models obtained showed that dipping time is the most influential variable followed by pressing temperature, whereas the pressing time was insignificant to all responses. The optimization of treatment conditions on the paper properties were carried out by employing response surface methodology (RSM) based on central composite design (CCD). Four response variables, namely density, burst index, smoothness, and rate of surface wettability were analyzed. Polynomial estimation model of each response was developed as functions of three independent variables, which are pressing temperature (T), dipping time (D), and concentration of cellulose acetate (C). The paper which was treated based on the calculated optimum condition (T: 163oC, D: 2.8 minutes and C: 2.7%) , possessed density of 0.5450 g/cm3, rate of surface wettability of 0.012o/s, burst index of 2.84-kPa m2/g, and paper smoothness of 475 mL/min. All the experimental values were significantly no different from the predicted values calculated from estimation models.